2003
DOI: 10.1023/b:thro.0000011372.26594.01
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a New Streptokinase Regimen with Enoxaparin in Acute Myocardial Infarction

Abstract: The accelerated streptokinase regimen was well tolerated and resulted in a significantly higher coronary reperfusion rate and significantly lower mortality compared with the traditional regimen. The 0.75 streptokinase + enoxaparin combination was at least as efficacious as the 0.75 streptokinase + UFH combination and is preferred because of its ease of administration and predictable anticoagulant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For patients with STEMI to be treated with fibrinolysis, 17 studies supported enoxaparin over UFH (LOE1 336,[387][388][389][390][391][392][393] ; LOE 2 341,394,395,396 ; LOE 4 397 ; LOE 5 393,396,398 -401 ) Twelve other studies were neutral comparing enoxaparin and UFH. [402][403][404][405][406][407][408][409][410][411] Reviparin. One study demonstrated improved clinical outcome with reviparin compared with UFH in STEMI patients treated with fibrinolysis (LOE 1).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For patients with STEMI to be treated with fibrinolysis, 17 studies supported enoxaparin over UFH (LOE1 336,[387][388][389][390][391][392][393] ; LOE 2 341,394,395,396 ; LOE 4 397 ; LOE 5 393,396,398 -401 ) Twelve other studies were neutral comparing enoxaparin and UFH. [402][403][404][405][406][407][408][409][410][411] Reviparin. One study demonstrated improved clinical outcome with reviparin compared with UFH in STEMI patients treated with fibrinolysis (LOE 1).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…After review of abstracts, an additional 16 studies were excluded. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] After review of the full article, an additional 8 studies were excluded because they were not properly randomized (nϭ3) [33][34][35] ; because at least 1 randomized treatment group did not receive aspirin (nϭ3) 36 -38 ; or because they were preliminary reports or the results of a substudy with the main results having been reported elsewhere (nϭ2). 39,40 Clinical outcome data could not be obtained for 1 additional study, 41 leaving 14 randomized trials, involving a combined total of 25 280 patients, for inclusion in the meta-analysis (Tables 1 to 3).…”
Section: Study Selectionmentioning
confidence: 99%
“…5 For understandable reasons related to the potential risk of hypotension (a well known specific effect of SK) and hemorrhagic complications, standard SK regimen (1.5 million units over 60 minutes) remained unchanged during last 15 years. 4 …”
Section: Discussionmentioning
confidence: 99%
“…However, some evidence points to the fact that a minimum dose of 500 U/kg/min may be needed for effective tissue level reperfusion, a dose that can not be obtained with such a relatively slow infusion over 60 minutes. 4 …”
Section: Introductionmentioning
confidence: 99%